Divergent responses to training load in professional Australian football: are insights obtained from generic and running-based assessments complementary or redundant? - Arguedas-Soley, A.; Shushan, T.; Murphy, A.; Poulos, N.; Lovell, R.; Norris, D. (Sports Medicine - Open, 2025)
Background Generic neuromuscular assessments are widely used to monitor training responses in team sports. Emerging running-based measures have been proposed to offer greater sensitivity to residual neuromuscular training effects by aligning more closely with the exercise dose, yet their practical utility remains ambiguous. Concurrent evaluation is thus necessary to identify athlete monitoring assessments that best capture meaningful responses.